Dystrophin Deficiency Causes Progressive Depletion of Cardiovascular Progenitor Cells in the Heart - Jelinkova, Sarka; Sleiman, Yvonne; Fojtík, Petr; Aimond, Franck; Finan, Amanda; Hugon, Gerald; Scheuermann, Valerie; Beckerová, Deborah; Cazorla, Olivier; Vincenti, Marie; Amedro, Pascal; Richard, Sylvain; et al. (International journal of molecular sciences, 2021)
Duchenne muscular dystrophy (DMD) is a devastating condition shortening the lifespan of young men. DMD patients suffer from age-related dilated cardiomyopathy (DCM) that leads to heart failure. Several molecular mechanisms leading to cardiomyocyte death in DMD have been described. However, the pathological progression of DMD-associated DCM remains unclear. In skeletal muscle, a dramatic decrease in stem cells, so-called satellite cells, has been shown in DMD patients. Whether similar dysfunction occurs with cardiac muscle cardiovascular progenitor cells (CVPCs) in DMD remains to be explored. We hypothesized that the number of CVPCs decreases in the dystrophin-deficient heart with age and disease state, contributing to DCM progression. We used the dystrophin-deficient mouse model (mdx) to investigate age-dependent CVPC properties. Using quantitative PCR, flow cytometry, speckle tracking echocardiography, and immunofluorescence, we revealed that young mdx mice exhibit elevated CVPCs. We observed a rapid age-related CVPC depletion, coinciding with the progressive onset of cardiac dysfunction. Moreover, mdx CVPCs displayed increased DNA damage, suggesting impaired cardiac muscle homeostasis. Overall, our results identify the early recruitment of CVPCs in dystrophic hearts and their fast depletion with ageing. This latter depletion may participate in the fibrosis development and the acceleration onset of the cardiomyopathy.
Keywords: DNA Damage; Aging; Dystrophin; myši inbrední mdx; kardiovaskulární systém; protoonkogenní proteiny c-kit; Gene Expression Regulation; poškození DNA; Disease Models, Animal; Cardiovascular System; genomic instability; Mice; mdx mouse; Myocytes, Cardiac; duchenne muscular dystrophy; regulace genové exprese; Proto-Oncogene Proteins c-kit; stárnutí; modely nemocí na zvířatech; myokard; zvířata; Humans; Cardiomyopathy, Dilated; dilatační kardiomyopatie; Myocardium; c-kit; dilated cardiomyopathy; Duchennova muskulární dystrofie; cardiovascular progenitors; myši; Stem Cells; Mice, Inbred mdx; kardiomyocyty; dystrofin; kmenové buňky; lidé; Muscular Dystrophy, Duchenne; Animals